COMMUNICATION FAILURES IN NETFLIX DRAMA SERIES â€œ13 REASONS WHYâ€: A PRAGMATIC ANALYSIS - Wulandari, Astri; Hapsari, Brigitta Shinta; Bram, Barli (Sanata Dharma University, 2018)
Language and linguistics are vital in peopleâ€™s daily conversation. However, because of some causes, there are some misunderstandings or pragmatic failures which may appear in communication among people. Many studies have looked into the pragmatic failures between native speakers and non-native speakers but this study investigates pragmatic failures in Netflix TV drama series â€œ13 Reasons Whyâ€. It aims to discover pragmatic failures that happened in the drama and their causes. To gather the data, the researchers watched the series and highlighted some events that contained pragmatic failures. Then, the researchers used three steps of data analysis: gather and organize, categorize, and analyze the findings. The findings showed that there were 25 pragmatic failures that happened in the drama. They were caused by five reasons, namely failure in understanding othersâ€™ intentions, failures in understanding othersâ€™ state, denials to the reality, trauma, and failures in understanding a situation.Â DOI:Â https://doi.org/10.24071/ijhs.2018.010212